Centre for Political and Related Terminology in Southern African Languages (CEPTSA) — Translating and Explanatory Dictionaries - Alberts, Mariëtta (Lexikos, 2015)
The Centre for Political and Related Terminology in Southern African Languages (CEPTSA) published the revised and amended bilingual translating version of the Modern Political Dictionary (MPD) in 2011, and immediately started to define core political terms. The phases of the project, consisting of different translating and explanatory versions, are discussed.The aim of CEPTSA is to promote the usage of political and related terminology in Southern Africa. Research is being done on these subject fields, and relevant concepts and terms are harvested, defined and translated. The source language is English and Afrikaans was initially the target language. The Centre, however, already compiled a list of 1000 core terms of the subject area in Tswana, Northern Sotho, Zulu and Xhosa. The Centre is currently busy with defining a further 1500 core terms and as soon as this process is finalised, the English/Afrikaans core terminology list and definitions will be published and the data translated into the official African languages.The Centre provides a terminological and subject-related service to lecturers and under- and postgraduate students in international politics, political studies and governance, public administration, municipal government and administration, development studies and strategic studies. A service is also rendered to members of parliament, provincial legislature and local authorities, language practitioners and the media.The Centre received several awards for the bilingual dictionaries already published, namely the Dictionary category of the South African Translators' Institute (SATI) (2003), the 'Woordfees' award of the Afrikaanse Taal- en Kultuurvereniging (ATKV) (Afrikaans Language and Cultural Association) (2006), and the Stals award of the Suid-Afikaanse Akademie vir Wetenskap en Kuns (South African Academy for Science and the Arts) (2010).